Pengacakan Soal Ujian Menggunakan Algoritma Linear Congruent Method - K, agus; Pawelloi, A. Irmayani; Selao, Ahmad (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
The use of multiple-choice exam questions in academic evaluations in schools is often fraudulent, such as cheating or student cooperation, which can reduce the validity of the assessment. This application is designed to randomize the order of questions and answer options automatically, so that each student gets a different question. Using qualitative methods based on black box testing and white box testing using laptop hardware, smartphones, and Windows 10, XAMPP, MySQL, and Visual Studio Code software. Test results show that this application is effective and efficient in randomizing questions and answer choices, minimizing cheating, preventing collaboration, and encouraging students to learn better.